112k views
4 votes
Solve the system of equations. y = 7x + 43 y = 2x + 13 a. ( -6, 1) c. ( 6, 1) b. ( 6, -1) d. No solution

1 Answer

4 votes
Hello there!

y = 7x + 43
y = 2x + 13

We wanna solve y = 7x + 43 for y in y = 2x + 13

What does that even mean? Well it simply means that we gonna replace y by 7x + 43.

y = 2x + 13

7x + 43 = 2x + 13

Subtract 2x on both sides

7x + 43 - 2x = 2x + 13 - 2x

5x + 43 = 13

Now we can subtract 43 on both sides

5x + 43 - 43 = 13 - 43

5x = -30

Then divide both sides by 5

5x/5 = -30/5

x = -6

Now since we have the value for x, we gonna use that value to find y.

We can do that by substituting -6 for x in y = 7x + 43

But what does that mean? It means that in y = 7x + 43, we gonna replace the x by -6

y = 7x + 43

y = 7(-6) + 43

y = -42 + 43

y = 1

Thus,

The answer is: x = -6 and y = 1

The correct answer is option A (-6,1).

Let me know if you have questions about the answer. As always, it is my pleasure to help students like you.
User Jitin
by
5.6k points